TEM study on the electrical discharge machined surface of single-crystal silicon - Murray, J.W.; Fay, M.W.; Kunieda, M.; Clare, A.T. (Elsevier, 2013)
EDM is a useful process for machining high-aspect ratio features with good accuracy in electrically conductive materials irrespective of their mechanical properties. With the ability of micro-EDM to compete with the resolution of conventional semi-conductor processing techniques, the process has attracted interest for the potential machining of single-crystal silicon. In order for the process to be feasible, the damage mechanism occurring during machining must be characterised to assess the need for secondary processing. Despite this the microstructural transformations induced by the process on the surface of the workpiece have not yet been assessed. In this study transmission electron microscopy (TEM) and laser-Raman spectroscopy are employed to characterise the microstructural changes as well as the presence of any contaminants and defects at the nano-scale. A twinned-crystalline structure created by epitaxial growth is formed in the recast layer. Some amorphous phase is also present. Findings indicate sub-surface pores between 10 nm and 200 nm diameter formed by gas expansion are observed. If the formation of such pores can be generalised for EDM processing of other materials, this phenomenon may contribute to the reduced mechanical integrity of such machined surfaces. Significant tool electrode material deposition with crystals of down to 3 nm diameter also occurred in the workpiece surface. The nano-scale of embedded material may have implications for the progress of electrical discharge machining as a coating process and the properties of such coatings.